Numerical simulation of nanofluid flow due to a stretchable rotating disk - Ayano, Mekonnen S.; Otegbeye, Olumuyiwa; Mathunjwa, Jochonia S. (Elsevier, 2023)
In this study, a steady magnetohydrodynamic (MHD) flow due to stretchable rotating disk in the presence of gyrotactic microorganisms is investigated. The governing equations modeling the flow are solved numerically using the newly introduced simple iteration method (SIM) that seeks to linearize a system using relaxation technique that effectively decouples the system. To verify the convergence and accuracy of the method, solution error and residual error analysis are carried out, respectively. The obtained results suggest that the SIM is a highly efficient method that produces convergent and highly accurate solutions. The effects of various parameters as well as combined parameter effects on the solution profiles are also investigated. An increase in the Hall and permeability parameters leads to a corresponding rise in the microorganism’s density and nanoparticle volume fraction.
Keywords: Stretchable rotating disk; Hall effect; Porous medium; Bioconvection; Relaxation; Spectral methods; SDG-17: Partnerships for the goals